Proceedings of the Workshop on Irrigation and Vector-Borne Disease Transmission - International Irrigation Management Institute; Joint WHO/FAO/UNEP Panel of Experts on Environmental Management for Vector Control (International Irrigation Management Institute, 1986)
Vector-borne diseases continue to be one of the predominant public health problems in Sri Lanka and other developing countries. Diseases such as malaria and filariasis pose an undeniable threat to the success of water resource development, and the role of preventive or mitigating measures is discussed as a priority in the planning, implementation, and management of irrigation projects.